EFFECT OF SELF EFFICACY AND ORGANIZATIONAL CITIZENSHIP BEHAVIORS ON EMPLOYEE SATISFACTION - Siti Samsiyah; Roza Monica Sintia Dewi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
Human resources become a major problem in various activities within a company, especially in the field of organizational. This research aims to test and analyze the employee satisfaction of PT. Sinar Karya Abadi's work which is influenced by the variable of self-efficacy and behavior of the citizenship organization. The population amounted to 500 employees and obtained samples amounting to 85 respondents consisting of employees of PT. Sinar Karya Duta Abadi. Simple random sampling is a sampling technique that uses the utility. Obtained data from the propagate then recollected the questionnaire and used techniques analyzed multiple linear regression and hypotheses tests. Available work satisfaction results gain influence from free variables. That result illustrates the free variables having an influence on the dependent variables. It is hoped that this research can be used as a reference where PT. Sinar Karya Duta Abadi can improve employee satisfaction through self-efficacy and behavior of the nationality organization, if the two traits are owned by each individual, then the organizational productivity increases.